Research and knowledge of human development - Pulkkinen, Lea (Annales Academiae Scientiarum Fennicae, 2023)
Concepts regarding human development have taken shape slowly. Empirical research of it began in the 19th century, inspired by the natural sciences. Childhood, youth, adulthood, and aging became a developmental continuum in the 20th century within life-span development theories. Human development research is a multidisciplinary task, and its results are applicable in practical work with humans. The article considers the use of research information in terms of its appreciation, expertise, supplementation, application, and dissemination. Knowledge of human development would support well-being and promote cooperation and life on our planet of limited resources, taking care of each other.